RISK FACTORS OF RECURRENCE LUMBAR INTERVERTEBRAL DISC HERNIATION AFTER PRIMARY ENDOSCOPIC TRANSFORAMINAL DISCECTOMY. PART 1 (LITERATURE REVIEW) - Kolesnichenko, Vira; Piontkovskyi, Valentin; Holbaum, Maksym; Chernyshov, Oleksandr; Palkin, Oleksandr; Palkin, Boris (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Percutaneous endoscopic transforaminal discectomy (PETD) is a minimally invasive technique that improves clinical outcomes. However, limited visibility of the surgical field and the widespread use of endoscopic technology have led to complications after discectomy, among which recurrence of lumbar disc herniation is the main reason for repeated surgical interventions. The aim is to study epidemiological risk factors that potentiate the recurrence of lumbar intervertebral disc herniation after primary percutaneous endoscopic transforaminal discectomy. Methods. The study material is professional articles containing the definition of epidemiological risk factors for recurrence of lumbar disc herniation after primary PETD, for the period 2015–2024. A systematic review of relevant literature sources was performed using the following keywords: "recurrent lumbar disc herniation", «risk factor for recurrent lumbar disc herniation», "minimally invasive lumbar spine surgery", "percutaneous endoscopic lumbar discectomy», "percutaneous endoscopic transforaminal discectomy», "re-discectomy". Results. Research data on the reliability of the relationship between the recurrence of lumbar disc herniation after primary PETD and epidemiological risk factors are contradictory. The most significant among them was older age, ruptures of the annulus fibrosus. Conclusions. The most reliable epidemiological risk factors for rGMD of PVC after primary PETD are age > 50 years, body mass index > 25 kg/m2. The reasonable time for performing primary PETD of lumbar disc herniation from a medical and financial point of view is ≤ 8 weeks from the moment of clinical manifestation of the disease.